2019
DOI: 10.1371/journal.ppat.1007959
|View full text |Cite
|
Sign up to set email alerts
|

SopF, a phosphoinositide binding effector, promotes the stability of the nascent Salmonella-containing vacuole

Abstract: The enteric bacterial pathogen Salmonella enterica serovar Typhimurium ( S . Typhimurium), utilizes two type III secretion systems (T3SSs) to invade host cells, survive and replicate intracellularly. T3SS1 and its dedicated effector proteins are required for bacterial entry into non-phagocytic cells and establishment and trafficking of the nascent Salmonella -containing vacuole (SCV). Here we identify the first T3SS1 effector required to main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 156 publications
(212 reference statements)
8
91
0
Order By: Relevance
“…Recent work identified SopF as a novel SPI1‐T3SS effector protein with roles in controlling the SCV integrity (Lau et al, ) and inhibition of the host cell xenophagic machinery by modifying subunit of the vATPase (Xu et al, ). These findings underline the critical importance of controlling SCV integrity and host cell response to intracellular Salmonella .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work identified SopF as a novel SPI1‐T3SS effector protein with roles in controlling the SCV integrity (Lau et al, ) and inhibition of the host cell xenophagic machinery by modifying subunit of the vATPase (Xu et al, ). These findings underline the critical importance of controlling SCV integrity and host cell response to intracellular Salmonella .…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella maintains the integrity of the SCV by actions of the SPI2-T3SS and its effector protein SifA, and sifAdeficient strains are highly attenuated in systemic virulence (Beuzon et al, 2000). This would argue against an overall importance of cyto- Recent work identified SopF as a novel SPI1-T3SS effector protein with roles in controlling the SCV integrity (Lau et al, 2019) and inhibition of the host cell xenophagic machinery by modifying subunit of the vATPase (Xu et al, 2019). These findings underline the critical importance of controlling SCV integrity and host cell response to intracellular Salmonella.…”
Section: Cytosolic Presence Of Salmonella-detour or Cul-de-sac?mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that a subfraction of S. Tm may escape the SCV over time and become cytosolic. 81,85 When we analyzed the cytosolic subpopulation with the help of S. Tm localizer , carrying a reporter for cytosolic escape (pCK100, glucose-6-phosphate (Glc6P)-driven expression of mCherry), [86][87][88][89] we found that at 7 hpi, around one quarter of all the cytosolic bacteria was FliC + (Fig S7B). Strikingly, we frequently detected bacteria with protruding flagella (Fig S7A, S7C).…”
Section: Introductionmentioning
confidence: 99%
“…Since most intracellular bacteria replicate inside the host, bacteria enumeration varies during the time course of an infection. More specifically, in in vitro infection models using Salmonella infected epithelial HeLa cells, bacterial enumeration estimates <10 bacteria per HeLa cell at early times and up to 100 bacteria at late times in infection [22].…”
Section: Introductionmentioning
confidence: 99%